Trends In The Improvement Of Social Entrepreneurship (Zien Journal of Social Sciences and Humanities, 2026)
This article analyzes the contemporary trends in the improvement of social entrepreneurship within the context of socio-economic transformations and the development of civil society institutions. The study examines theoretical approaches to social entrepreneurship, its social mission, economic sustainability, and innovative characteristics. Particular attention is paid to the role of social entrepreneurship in addressing social inequalities, promoting inclusive development, reducing unemployment, and enhancing community welfare. Using qualitative and comparative research methods, the article identifies key factors influencing the effectiveness of social entrepreneurial initiatives and explores international experiences that may contribute to the advancement of social entrepreneurship in developing countries. The findings demonstrate that the integration of innovation, digital technologies, social responsibility, and stakeholder cooperation significantly enhances the sustainability and social impact of social enterprises. The article concludes that social entrepreneurship is becoming an increasingly important mechanism for achieving sustainable development goals and strengthening social cohesion